A facile preparation of functional cycloalkynes via an azide-to-cycloalkyne switching approach. Issue 24 (7th March 2019) - Yoshida, Suguru; Kuribara, Tomoko; Ito, Harumi; Meguro, Tomohiro; Nishiyama, Yoshitake; Karaki, Fumika; Hatakeyama, Yasutomo; Koike, Yuka; Kii, Isao; Hosoya, Takamitsu
Abstract : Terminal alkyne-selective click conjugation of diynes bearing strained and terminal alkyne moieties with functional azides has been achieved by transient protection of strained alkynes via complexation with copper to easily afford various functional cycloalkynes. Abstract : A facile method for preparing various functional cycloalkynes, including proteins incorporated with a cycloalkyne moiety, from the corresponding azides is developed. Treatment of diynes bearing strained and terminal alkyne moieties with a copper salt enabled terminal alkyne-selective click conjugation with azides, whereas a more azidophilic strained alkyne moiety was transiently protected from the click reaction via complexation with copper.